Engaging Political Pentecostalism: A Probe into the Political Theology of a Post-Confessional Christian Network - Leandro Luis Bedin Fontana (Religions)
The phenomenon conceptualized in this paper as political pentecostalism is described as a post-confessional Christian network of religious leaders and megachurches that has transformed the political scene on a global scale in the last decades. This new development represents a point of inflection in many respects within the trajectory of modern societies, particularly in the Global South, and adds new challenges to the already vexed relation between religion and civil society. Methodologically, this paper sets out to systematize the results of extensive ethnological studies about this phenomenon with the aim of reconstructing its genealogy, capturing its distinctive phenomenological traits, and distilling its central theological tenets. Defining the latter along the lines of spiritual warfare, dominion theology, and over-realized eschatology constitutes the condition for establishing as well as engaging its underlying political theology, which will be appraised in the last section. The criticism leveled there with the aid of the concepts of katechon, sovereignty, and common good is indicative of the necessity of a broader theological debate, given the multiple inconsistencies contained in its political theology, while being aware of the challenges that they pose to Christian theology as a whole.